The Root Of Islamic Fundamentalism in The Political Thoughts Of Al-Maududi and Sayyid Qutb: A Historical Study - Ilman Nafia; Septi Gumiandari (Jurnal Tamaddun : Jurnal Sejarah dan Kebudayaan Islam, 2019)
AbstractAl-Maududi and Qutb are two Islamic thinkers who are often claimed to be figures of Islamic fundamentalism. The thoughts of these two figures are strongly suspected have an influence on the emergence of the spirit of fundamentalists in various parts of the Islamic world to establish an Islamic state. It is here that the significance of the historical study of Islamic political thought of the two figures is important to reveal. Through a literature review, this paper aims to find out the differences and similarities in the political vision between al-Maududi and Sayyid Quthb regarding the form of the State. The results of the text review of the thoughts of the two figures show that both ideas characterized more constructive suggestions for the administration of an Islamic state, rather than offering a concrete form of government. Although both have a similar obsession about the Islamic state, the strategies adopted by both of them in reaching their obsession have differences. Maududi was more inclined to the form of cultural movements, while Qutb was more likely to choose revolutionary movement.Key Words: Islamic Fundamentalism, Political Thought, History